Factor the following expression:
4x + 2
2(2x + 1)
Convert the following equation to the standard form:
12x2 + 4x = 3
12x2 + 4x - 3 = 0
Substitute appropriate values for letters in the quadratic formula: 2x2 - 4x + 5 = 0
x =
(-(-4) +-sqrt((-4)^2-4(2)(5)))/(2(2))
Solve the Following Equation:
(x - 2)(x + 7) = 0
x = 2, -7
Factor the following Equation
x2 + 3x + 2 = 0
(x + 2)(x + 1) = 0
Factor the following expression:
x2 - 9
(x + 3)(x - 3)
Convert to the standard form:
-x2 = 14x - 8
0 = x2 + 14x - 8
Use the quadratic formula to solve the equation:
2x2 + 4x - 3 = 0
x=(-4 +-sqrt40)/4
Solve the following Equation:
(2x - 4)(x - 1) = 0
x = 1, 2
Solve by factoring:
x2 + 7x + 10 = 0
x = -5, -2
Factor the following expression:
12x - 3x2
3x(4 - x)
Convert to the standard form:
2x2 + 2x = 5 - 3x2
5x2 + 2x - 5 = 0
Solve the equation using quadratic formula:
6x2 − x = 5
x =
-5/6, 1
Solve the equation:
(3x - 1)(5x + 4) = 0
x =
-4/5, 1/3
Solve the equation by factoring
x2 - 5x - 14 = 0
x = -2, 7
Factor the following expression:
8x2 - 18
2(2x - 3)(2x + 3)
Convert to the standard form:
12x2 + 5x - 3 = 8x2 - 2x - 3
4x2 + 7x = 0
Solve the following equation, use quadratic formula:
x2 − 16x = 2x - 81
x = 9
Solve the Following Equation:
5(4x - 6)(2x + 10) = 0
x = -5, 1.5
Solve the equation by factoring:
3x2 - 10x + 7 = 0
x =
7/3, 3